Proceedings of the 41st Annual Hawaii International Conference on System Sciences (HICSS 2008) 2008
DOI: 10.1109/hicss.2008.96
|View full text |Cite
|
Sign up to set email alerts
|

Conceiving Interoperability between Public Authorities A Methodical Framework

Abstract: An increasing level of cooperation between public administrations nowadays on national, regional and local level requires methods to develop interoperable EGovernment systems and leads to the necessity of an efficient modeling of collaborative business processes and their implementation. In this paper a framework to systematically develop interoperable systems in the public sector is described. The methodology is motivated and explained on the basis of an E-Government reference model for the German Plan Approv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…1) Cost/economics drive: although e-government aims to improve efficiency, effectiveness, cost and transparency, no studies have been found within the list of selected articles that consider economic aspects. 1 (1,9%) Framework [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65] 24 (46,2%) Ontology -0 (0%) Metamodel [31] 1 (1,9%) Conceptual Model [66], [36], [35], [67], [34], [33], [32] [68], [69], [70], [71], [72], [73], [74], [75], [40], [76], [77], [39] , [38], [78], [37] [79], [80] 2) Value drive: four articles (7,7%) aimed at adding value on issues such as improving decision making and ...…”
Section: ) Model Focusmentioning
confidence: 99%
See 2 more Smart Citations
“…1) Cost/economics drive: although e-government aims to improve efficiency, effectiveness, cost and transparency, no studies have been found within the list of selected articles that consider economic aspects. 1 (1,9%) Framework [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65] 24 (46,2%) Ontology -0 (0%) Metamodel [31] 1 (1,9%) Conceptual Model [66], [36], [35], [67], [34], [33], [32] [68], [69], [70], [71], [72], [73], [74], [75], [40], [76], [77], [39] , [38], [78], [37] [79], [80] 2) Value drive: four articles (7,7%) aimed at adding value on issues such as improving decision making and ...…”
Section: ) Model Focusmentioning
confidence: 99%
“…[40]) or presented descriptive studies of administrative situations that were presented as models (e.g. [39], [63]), so they were classified in this category. The most addressed model focus has shifted, from Technology and Organization & Process (2008 to 2013) towards Citizen and (some) Technology; strikingly, the initially codominant Organizational & Process has vanished from the literature.…”
Section: ) Model Focusmentioning
confidence: 99%
See 1 more Smart Citation
“…Karagiannis and Hofferer [17] have performed a survey looking at the use of meta-models to integrate processed across organizations. Ziemann et al [30] propose a framework to model and transform cross-organizational business processes to technical process model based on web service protocols. The approach involves establishing process descriptions using Event Process Chains (EPC), which is further converted to BPEL syntax.…”
Section: Inter-organizational Collaborationmentioning
confidence: 99%
“…We further know that providing citizen-centric organization of services require changes in technology, changes that can significantly affect the direction and progress of applications development, by either enhancing or limiting choices or functionality [30]. Based on that we will discuss the possibilities of an adaptive infrastructure and organization supporting delivery of evolving e-services.…”
Section: Introductionmentioning
confidence: 99%